THE CONCEPT OF COMMUNITY AND ITS RELATIONSHIP WITH EDUCATION - Fitriani Syamal; Firman; Riska Ahmad (Literasi Nusantara, 2021)
This article discusses the concept of the nature of society and its relation to education. Society is a group of living things that are closely intertwined because of certain systems, certain traditions, conventions and certain laws in common, and lead to collective life. People's personalities are formed through the amalgamation of individuals and their cultural actions and reactions. Education is very important in life because it can improve human quality, but there are still many people who do not realize the importance of education. Families, schools and communities will be the center of activities in the implementation of education.